2012
DOI: 10.1371/journal.pone.0048966
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) in Paraventricular Nucleus Modulates Sympathetic Activity and Cardiac Sympathetic Afferent Reflex in Renovascular Hypertensive Rats

Abstract: BackgroundExcessive sympathetic activity contributes to the pathogenesis and progression of hypertension. Enhanced cardiac sympathetic afferent reflex (CSAR) is involved in sympathetic activation. This study was designed to determine the roles of angiotensin (Ang)-(1–7) in paraventricular nucleus (PVN) in modulating sympathetic activity and CSAR and its signal pathway in renovascular hypertension.Methodology/Principal FindingsRenovascular hypertension was induced with two-kidney, one-clip method. Renal sympath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 52 publications
(69 reference statements)
1
25
0
Order By: Relevance
“…Beside the work by Tallant and Clark 21 and by Liu et al 22 in primary cells, an article from 2012 showed indirect cAMP involvement in Ang-(1-7) signaling because its modulation of sympathetic activity in the paraventricular nucleus was abolished by an AC inhibitor and a PKA inhibitor. 31 Furthermore, physiological effects of the heptapeptide and effects in preclinical models also implicate the involvement of cAMP. For example, we demonstrated the dominant effect of Ang-(1-7) on hematopoietic stem cells/progenitors, 32 and there is a significant evidence that cAMP stimulates such processes.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the work by Tallant and Clark 21 and by Liu et al 22 in primary cells, an article from 2012 showed indirect cAMP involvement in Ang-(1-7) signaling because its modulation of sympathetic activity in the paraventricular nucleus was abolished by an AC inhibitor and a PKA inhibitor. 31 Furthermore, physiological effects of the heptapeptide and effects in preclinical models also implicate the involvement of cAMP. For example, we demonstrated the dominant effect of Ang-(1-7) on hematopoietic stem cells/progenitors, 32 and there is a significant evidence that cAMP stimulates such processes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, A-779 injections into the PVN have been shown to attenuate hypertension induced by a sleep apnea model in rats (108), which agrees with the sympathetic stimulatory effect of acute injections of ANG-(1-7) into the PVN. Nevertheless, ANG-(1-7) injections into the PVN effectively increased the RSNA, CSAR, and arterial pressure through an activation of MAS via the cAMP-PKA pathway (237,307,308,527,640). However, these studies were performed in anesthetized vagotomized and sinoaortic denervated rats, a condition that may introduce important changes in the activity of PVN neurons and their sensitivity to neuromodulators.…”
Section: Cardiovascular Effects Of Angiotensin-(1-7) At Specific Hypomentioning
confidence: 99%
“…This AAR has been extended recently to other WAT pads, but with renal sympathetic nerve activity increases (adipose afferent renal reflex, AARR) with related changes in blood pressure and other cardiovascular responses (19,22,35,42,55,66,67).…”
Section: R896mentioning
confidence: 99%